Age-Dependent Changes of Adipokine and Cytokine Secretion From Rat Adipose Tissue by Endogenous and Exogenous Toll-Like Receptor Agonists - Peek, Verena; Neumann, Elena; Inoue, Tomohiro; Koenig, Sandy; Pflieger, Fabian Johannes; Gerstberger, Rüdiger; Roth, Joachim; Matsumura, Kiyoshi; Rummel, Christoph (Frontiers in Immunology, 2020)
White adipose tissue but recently also brown adipose tissue have emerged as endocrine organs. Age-associated obesity is accompanied by prolonged and elevated lipopolysaccharide (LPS)-induced sickness symptoms and increased cytokine and adipokine levels in the circulation partially originating from adipose tissue. In the present study, ex vivo fat explants were used to investigate how the exogenous pathogen associated molecular pattern (PAMP) LPS or the endogenous danger associated molecular patterns (DAMPs) high mobility group box-1 protein (HMGB1) and biglycan modulate the release of cytokines and adipokines / batokines and, thus, could influence systemic and/or local inflammation. The response of adipose tissue (epididymal, retroperitoneal, subcutaneous and brown) was compared between young lean and old obese rats (2 versus 24 months old). LPS induced a strong interleukin (IL)-6 and tumor necrosis factor (TNF)alpha release into the supernatant of all adipose tissue types investigated. HMGB1 (subcutaneous) and biglycan (retroperitoneal) led to an increased release of IL-6 and TNFalpha (HMGB1) and decreased visfatin and adiponectin (biglycan) secretion from epididymal adipose tissue (young rats). Visfatin was also decreased by HMGB1 in retroperitoneal adipose tissue of old rats. We found significantly higher leptin (all fat pads) and adiponectin (subcutaneous) levels in supernatants of adipose tissue from old compared to young rats, whereas visfatin secretion showed the opposite. The expression of the biglycan receptor Toll-like receptor (TLR)2 as well as the LPS- and HMGB1-receptors TLR4 and receptor for advanced glycation endproducts (RAGE) were reduced with age (TLR4 / RAGE) and by stimulation with their ligands (subcutaneous). Overall, we revealed that adipokines/adipose-tissue released cytokines show some modulation of their release caused by mediators of septic (batokines) and sterile inflammation with potential implication for acute and chronic disease. Moreover, aging may increase or decrease the release of fat-derived mediators. These data show that DAMPS and LPS locally modulate cytokine secretion while only DAMPS but not LPS can locally alter adipokine secretion during inflammation.